Pengaruh Pendidikan Kewirausahaan dan Stereotip Gender terhadap Intensi Kewirausahaan Mahasiswa yang dimediasi oleh Kebutuhan Berprestasi dan Efikasi Diri ( Studi pada Mahasiswa asli Papua di Jayapura) - Bharanti, Bonifasia Elita; Idrus, M.S; Zain, Djumilah; ., Solimun (Universitas Brawijaya, Indonesia, 2012)
The study is aimed to test and analyze the influence of entrepreneurship education towards the student' entrepreneurial intentions both directly and indirectly through the needs for achievement and self- efficacy and the influence of gender stereotype towards the student entrepreneurial intentions both di- rectly and indirectly through the needs for achievements and self-efficacy. The Population of study wa the native Papua student who having certain economic background in Jayapura. The sample was selected from 197 of 4 (four) universities in Jayapura. The sampling technique used was probability sampling with proportionate stratified random sampling and the data analysis was conducted using SEM (Structural Equation Model) and Sobel Test. The Result of analysis show that the entrepreneurship education can improve the students' entrepreneurial intentions indirectly as self-efficacy increased. Whereas gender ste- reotype can improve students' entrepreneurial intentions both directly and indirectly as the needs for achievement and self-efficacy increased. Gender stereotype gives major contribution to the increase of students' entrepreneurial intentions.